1984
DOI: 10.1007/bf00266836
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of tendolipomatosis; an electron microscopical study

Abstract: The development of tendolipomatosis has been studied both by light and scanning electron microscopy in the tendons of healthy persons killed in accidents. Lipid cells are rarely seen in the intact tendon. In the early stages of tendolipomatosis lipid cells are found deep and singly but in the later phases lipocytes are seen to disrupt the continuity of collagen fibres and tendon bundles and so reduce the strength of the tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 4 publications
1
18
0
1
Order By: Relevance
“…Jozsa et al demonstrated this as lipid deposits along collagen fibrils which were observed utilizing electron microscopy, possibly disrupting the structural integrity of the tendon and making it more prone to tendon rupture or injury. 60 …”
Section: Hypercholesterolemiamentioning
confidence: 99%
“…Jozsa et al demonstrated this as lipid deposits along collagen fibrils which were observed utilizing electron microscopy, possibly disrupting the structural integrity of the tendon and making it more prone to tendon rupture or injury. 60 …”
Section: Hypercholesterolemiamentioning
confidence: 99%
“…The lipomatous tendon seems to be a combination of normal structures with variable areas of lipid cells. Around the lipocytes, a dense reticular network of thin, type I11 collagen fibers can be found (26). As the accumulation of lipid cells expands, they form chains and three-dimensional conglomerations (1,5).…”
Section: Tendolipomatosismentioning
confidence: 99%
“…These include dyslipidemia, hypertension, glucose intolerance, and insulin resistance (5,25,28). Because lipid deposition is known to occur in tendons (1,11), high cholesterol levels have been observed among individuals with Achilles tendon rupture (19,22), and the esterified fraction of cholesterol is elevated in biopsies from Achilles tendinopathy subjects (29) we chose to focus on serum lipid profiles.…”
mentioning
confidence: 99%